Integrating Robotic Fabrication into the Basic Design Studio - Yazar, Tuğrul; Oral-Karakoç, Hülya; Gündüz, Gamze; Yabanigül, Meryem N. (Springer Science and Business Media LLC, 2023)
Digital fabrication technologies are revealing new ways of dealing with design processes. Robotic fabrication technologies are generally dismissed at the undergraduate level, especially in first-year design education. This is due to the common belief that novice design students have insufficient skills for designing with a robotic arm. This paper presents an experiment that took place in a first-year basic design studio at a faculty of architecture. The studio investigates the utilization of a robotic arm as a design and production tool. Students without robot programming and operation skills were encouraged to transfer a priori skills of hand tools and techniques learned in successive assignments to utilize the robotic arm. This experiment revealed the educational potential strategies for the integration of robot technology in first-year design studios.
Keywords: Robotic arm; Basic design; Digital fabrication; learning-by-doing; material computation